Reflections of a Social Justice Counselor in Training: What Action Research Has Meant to Me - Amy Johnson Howton (Journal for Social Action in Counseling and Psychology, 2011)
This article details my professional identity development as a social justice counselor and the role that action research has played in supporting my development. As an action researcher and social justice counselor, I have come to understand my location in the larger field of counseling as an “outsider-within” (Collins, 1990), positioned in the “borderlands” (Anzaldua, 1987) of the field. Action research helped me to understand how this positioning creates both opportunity and challenge for me personally and professionally. I describe three key lessons learned from my work as an action researcher that translate to my envisioned role as a counselor: 1) the impact of power and privilege on relationships 2) the significance of the process itself, and finally, 3) change is messy. I argue that my own struggle to secure for myself a sense of place and legitimacy within the field of counseling reflects a similar struggle to that being experienced by social justice counseling in general within the larger field of counseling.